Effect of pulsed electric field on electrodialysis of a NaCl solution in sub-limiting current regime. (10th May 2015) - Sistat, P.; Huguet, P.; Ruiz, B.; Pourcelly, G.; Mareev, S.A.; Nikonenko, V.V.
Graphical abstract: Highlights: A 1D model based on the Nernst–Planck equations and the electroneutrality assumption adequately describes pulsed electric field (PEF) electrodialysis at sub-limiting currents. The mass transfer rate in PEF mode increases with increasing frequency and decreasing duty cycle. Instantaneous current density may be higher than the limiting current, j lim, in DC conditions. The average mass transfer at frequencies >1 Hz is higher than that in DC conditions, but within the model it cannot be higher than j lim . Abstract: In spite of growing applications of pulsed electric fields (PEF) in membrane separation processes, there are only few theoretical studies treating mass transfer. In this paper, we propose a 1D mathematical model, which adequately describes PEF mode electrodialysis (ED) with ion-exchange membranes at sub-limiting currents. The results of simulation are compared with experimental data obtained for a laboratory-scale electrodialysis stack. We show experimentally and theoretically that the average current density and mass transfer under PEF of a sufficiently high frequency (>1 Hz in the used conditions) are higher than those in conventional steady state DС mode, if a same average voltage is applied. The advantage increases with frequency and reaches a maximum at about 100 Hz. When applying a pulse after a pause, we benefit by low ohmic resistance and low diffusion potential drop caused by partial concentration restoration in close vicinity of the membrane. This allows passage of an instantaneous current of a high density, which can essentially exceed the limiting current density ( j lim ) in steady state DC conditions. However, at low frequencies this gain rapidly vanishes by increasing concentration polarization during the pulse, thereby the mass transfer in PEF mode is lower than that in DС mode. The gain is close to zero at low currents due to linearity of I–V curve and increases with increasing current. However, within the model, the average current density cannot be higher than i lim . The gain in mass transfer rate at high frequencies increases with decreasing duty cycle, but with this the energy consumption for electrodialysis desalination in PEF mode increases, it is always higher than the energy consumption in continuous DС mode.